Characterisation and Properties of Sintered Recycled Glass utilising CIP Method - Nur Rifhan , Rosli; Azizah , Shaaban; Jariah , Mohamad Juoi; Nur Farizan , Ayoob (Trans Tech Publications, Switzerland, 2011)
Recycling glass is chosen as an alternative raw material in upgrading ceramic into glass ceramic. The main objectives are to determine the effect of sintering temperature and the recycled glass to ball clay weight ratio on glass ceramic produced from recycled glass. The recycled glass powders are prepared by crushing and grinding waste glass bottles to a particles size distribution below than 75 μm. The raw materials (recycled glass powder and ball clay) are characterised by Differential Thermal Analysis (DTA) and its composition is determine by X-Ray Fluorescence (XRF). The recycled glass powder are then mixed with the ball clay according to the ratio of SLSG to ball clay of 95:5 wt.%, 90:10 wt.% and 85:15 wt.%. Green samples of glass ceramic are then fabricated using Cold Isostatic Pressing (CIP) with constant pressure at 40 MPa. Sintering process is conducted at three different temperatures at 750°C, 850°C and 950°C with 1 h holding time. The sintered glass ceramic were then characterised using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) analyses. Results of physical analyses and microhardness testing conducted according to ASTM C 373 and ASTM C 1327 showed that better properties is achieved at batch composition compromised of 85:15 wt.% ratio of recycling glass to ball clay and sintered at 850 °C. SEM micrographs showed that samples produced from this optimum batch composition provide more homogeneous and dense surface. Furthermore, XRD analysis indicates that crystalline phases evolved during sintering contributes to the final strength of the glass ceramic. These encourage further development on the glass ceramic samples which intended for structural applications.